Evaluation of Fundamental d-q Synchronous Reference Frame Harmonic Detection Method for Single Phase Shunt Active Power Filter - Samir Gautam; Pei Yunqing; Yubaraj Kafle; Muhammad Kashif; Saad Ul Hasan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Active Power Filter has become popular choice to address the harmonic pollution present in power system. It relies on fast and accurate detection of reference current to guarantee efficient compensation performance. In this paper harmonic extraction using d-q Synchronous Reference Frame (SRF) for single phase system and various aspects defining its performance is presented. The effect of the orthogonal signal generation on the harmonic current extraction is analyzed. Three different filtering approaches are compared based on their time and frequency domain characteristics. The effect of DC offset in the measured load current, introduced during measurement and data processing is derived. Accordingly a novel method to eliminate this DC offset is proposed with minimum compromise on the dynamics of the system.  The discussions presented are validated using simulation results.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.4723